Regioselective Reaction of 2-Indolylmethanols with Enamides - Yuting Tian; Dongqing He; Limei Gao; Yu Zou; Xiaoshuang Liu; Qiang Wang; Enxiang Liang; Yongsheng Zheng (Molecules, 2023)
A highly regioselective reaction of 2-indolylmethanols with enamides has been developed at room temperature by using AlCl3 as a catalyst. A wide range of hybrids (40 examples) of indoles and enamides were obtained in moderate to good yields (up to 98% yield). This transformation represents the efficient way to introduce biologically important indoles and enamides skeleton into structurally complex hybrids.